Profil Metakognisi Mahasiswa dalam Memecahkan Masalah Aljabar Linear Elementer Ditinjau dari Gaya Kognitif Konseptual Tempo - Kartika, Dwiani Listya; Muhassanah, Nuraini (Edumatica : Jurnal Pendidikan Matematika, 2023)
Metacognition is one of the factors that influences students' success in solving mathematical problems. On the other hand, the reality in the field is that students experience difficulties in solving mathematical problems related to Elementary Linear Algebra because they contain a lot of repetitive calculations, so they require high levels of perseverance and accuracy. This research aims to describe students' metacognitive profiles in solving Elementary Linear Algebra problems in terms of cognitive style. The cognitive style chosen is the conceptual cognitive style of pacing through Matching Familiar Figures Tests with research subjects being mathematics students at Nahdlatul Ulama University, Purwokerto. The resulting metacognition profile was obtained from Elementary Linear Algebra problem-solving test data and interviews, which were analyzed and concluded through a series of method triangulation processes. The research results show that students are reflective and impulsive in carrying out all activities that are indicators of metacognitive awareness and regulation, as well as several indicators from metacognitive evaluation. Fast, accurate students carry out all activities that become indicators of metacognitive awareness, regulation, and evaluation. Meanwhile, slowly, inaccurate students carry out all activities that are indicators of metacognitive awareness and several indicators of metacognitive regulation but still need to be able to carry out activities of metacognitive evaluation.